The influence of communication satisfaction on job satisfaction - the case of employees in the Republic of Serbia - Biljana Djordjevic; Sandra Milanovic; Jelena Stankovic (Economic Horizons, 2021)
Communication is one of the processes that take place within a company. However, employees may be more or less satisfied with the communication that takes place in their work environment. Thus, if employees are satisfied with communication inside their company, such communication satisfaction can be expected to have a positive impact on job satisfaction (JS). Employee JS can initiate many other positive consequences in terms of their attitudes and behaviors. One way to achieve this is to increase satisfaction with internal communication. Starting from the above-mentioned, the subject matter of this paper is to examine the relationship between communication satisfaction (CS) and JS on the example of employees in companies in the Republic of Serbia. This research study is aimed at determining whether there is a connection between these phenomena or not. The sample consists of 202 employees. The results of the study have shown that the bivariate correlation between CS and JS is positive. In addition, the results of the study have shown that several dimensions of CS have a statistically significant impact on employee JS